Narratives of Two Indonesian Lecturers about Challenges of Writing an Undergraduate EFL Thesis - Yustinus Calvin Gai Mali (Universitas Muhammadiyah Yogyakarta, 2023)
The literature has overwhelmingly explained challenges in writing the undergraduate thesis from students’ perspectives. Yet, there is a scarcity of research that presents the perspectives of thesis supervisors about the challenges experienced by their EFL students and, at the same time, on possible solutions to solve them. This qualitative study presented two English as a Foreign Language (EFL) lecturers’ narratives on challenges EFL students experienced when writing their undergraduate thesis and on solutions to deal with those challenges. The research data was collected through a reflective essay written by the lecturers, who then met in an online synchronous meeting to discuss what they wrote in the essay. While the data analysis communicated various things, the students’ challenges in writing their undergraduate thesis were commonly about finding a research topic, writing the literature review, and using various academic vocabulary. In light of the results, possible solutions to solve the challenges, practical recommendations for EFL thesis writing and teaching activities, and guiding questions for further research were presented. This study should benefit EFL thesis supervisors to reflect on their own experiences, find areas for improvement and enhance their thesis supervisory practices. This study also hopes to benefit EFL students who wish to learn practical strategies to progress with their undergraduate thesis.